The ‘green’ start-up: environmental commitment and its impact on start-up success - Bardaa, Wafa (2022)
A Master of Science thesis in Finance by Wafa Bardaa entitled, “The ‘green’ start-up: environmental commitment and its impact on start-up success”, submitted in December 2022. Thesis advisor is Dr. Christian Rauch. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).